Systemic delivery of engineered compact AsCas12f by a positive-strand RNA virus vector enables highly efficient targeted mutagenesis in plants - Ishibashi, Kazuhiro; Sukegawa, Satoru; Endo, Masaki; Hara, Naho; Nureki, Osamu; Saika, Hiroaki; Toki, Seiichi (Frontiers in Plant Science, 2024)
Because virus vectors can spread systemically autonomously, they are powerful vehicles with which to deliver genome editing tools into plant cells. Indeed, a vector based on a positive-strand RNA virus, potato virus X (PVX), harboring SpCas9 and its sgRNA, achieved targeted mutagenesis in inoculated leaves of Nicotiana benthamiana. However, the large size of the SpCas9 gene makes it unstable in the PVX vector, hampering the introduction of mutations in systemic leaves. Smaller Cas variants are promising tools for virus vector-mediated genome editing; however, they exhibit far lower nuclease activity than SpCas9. Recently, AsCas12f, one of the smallest known Cas proteins so far (one-third the size of SpCas9), was engineered to improve genome editing activity dramatically. Here, we first confirmed that engineered AsCas12f variants including I123Y/D195K/D208R/V232A exhibited enhanced genome editing frequencies in rice. Then, a PVX vector harboring this AsCas12f variant was inoculated into N. benthamiana leaves by agroinfiltration. Remarkably, and unlike with PVX-SpCas9, highly efficient genome editing was achieved, not only in PVX-AsCas12f-inoculated leaves but also in leaves above the inoculated leaf (4th-6th upper leaves). Moreover, genome-edited shoots regenerated from systemic leaves were obtained at a rate of >60%, enabling foreign-DNA-free genome editing. Taken together, our results demonstrate that AsCas12f is small enough to be maintained in the PVX vector during systemic infection in N. benthamiana, and that engineered AsCas12f offers advantages over SpCas9 for plant genome editing using virus vectors.